Cross-resistance of the chloroquine-derivative AQ-13 with amodiaquine in Cambodian Plasmodium falciparum isolates. (10th July 2021) - Nardella, Flore; Mairet-Khedim, Mélissa; Roesch, Camille; Maher, Steven P; Ke, Sopheakvatey; Leang, Rithea; Leroy, Didier; Witkowski, Benoit
Abstract: Background: Expanding resistance to multiple antimalarials, including chloroquine, in South-East Asia (SEA) urges the development of new therapies. AQ-13, a chloroquine derivative, is a new drug candidate for treating malaria caused by Plasmodium falciparum. Objectives: Possible cross-resistance between the 4-aminoquinolines amodiaquine, piperaquine and AQ-13 has not been assessed. In vitro parasite growth assays were used to characterize the susceptibility of multidrug-resistant and susceptible P. falciparum patient isolates to AQ-13. Methods: A [ 3 H]hypoxanthine uptake assay and a 384-well high content imaging assay were used to assess efficacy of AQ-13 and desethyl-amodiaquine against 38 P. falciparum isolates. Results: We observed a strong cross-resistance between the chloroquine derivative amodiaquine and AQ-13 in Cambodian P. falciparum isolates (Pearson correlation coefficient of 0.8621, P <  0.0001). Conclusions: In light of the poor efficacy of amodiaquine that we described recently in Cambodia, and its cross resistance with AQ-13, there is a significant risk that similar clinical efficacy of AQ-13-based combinations should be anticipated in areas of amodiaquine resistance.